Clinical and etiological profile of neonatal seizures: a tertiary care hospital based study - Aziz, Asif; Gattoo, Imran; Aziz, Munazza; Rasool, Ghulam (International Journal of Research in Medical Sciences, 2017)
Background: The most vulnerable period of life to develop seizures is the neonatal period. These events very often signify serious damage or malfunction of the immature developing central nervous system. Neonatal seizures may arise as a result of diverse etiologies and can have varied presentations. Objective: Our study was aimed at finding the incidence, etiological factors, and time of onset, clinical types and various biochemical abnormalities in neonatal seizures. Methods: A hospital based prospective observational study was undertaken in a tertiary care paediatric hospital of Government Medical College Srinagar. A total of 100 consecutive neonates presenting with seizures from September 2013 to August 2014 were enrolled in the study. Detailed antenatal history and baseline characteristics of convulsing neonate were recorded at admission. Clinical details of each seizure episode reported by the mother and subsequently observed by the resident doctors on duty were recorded. Venous blood was collected as soon as possible and blood glucose, total serum calcium levels, Na+, K+, Mg and P-levels were done immediately after baby had seizures and before instituting any treatment. Data was described as mean ± SE and %age. SPSS 16.0 and MS Excel software were used for data analysis. Results: Cumulative frequency of 3.9% was recorded in neonatal seizures in our setup. Hypoxic ischemic encephalopathy was the commonest etiology of neonatal seizures. Intracranial haemorrhage followed by Hypoxic ischemic encephalopathy was the commonest seizure etiology in preterm neonates. Majority of Hypoxic ischemic encephalopathy patients presented with seizures in the first 72 hrs. of life. Focal clonic and subtle seizures were the commonest seizure types encountered. 17 neonates (31%) had primary metabolic seizures. Hypocalcaemia was the commonest biochemical abnormality in primary metabolic seizures and was present in 70% neonates in this group. Hypoglycaemia was the next commonest abnormality and was present in 41% neonates within this group. Conclusions: Hypoxic ischemic encephalopathy was the commonest etiology with focal clonic and subtle seizures being the commonest clinical types encountered. Hypocalcaemia was the most frequent biochemical abnormality found.